PERSONALITY TYPE IN TERE LIYE’S NOVEL NEGERI PARA BEDEBAH - Arif Fathurrahman Hutapea; M Manugeren; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2023)
This study is based on Tere Liye's novel Negeri Para Bedebah, which deals with personality types. Thomas or Tommi is a professional financial consultant and the founder of Thomas Co., a major financial consulting firm. Thomas is a one-of-a-kind individual since his co-workers regard him as adaptable. Thomas has a labile personality in the sense that his behavior is unpredictable and also changeable, adjusting to a certain situation. The grand theory used to support the whole research is the one proposed by Gerard Heymen, in which it is stated that every individual’s personality is unique and could be adjusted to a certain condition. Literary psychology is applied as an approach in the study, as literary psychology conducts literary studies by looking at literary works as psychological activities for both the author and the readers. The study is conducted by the descriptive qualitative method, showing the personality of the main character; this is a type of individual phenomenon that can also be found in society. The results show that the protagonist has three significant types of personality: smartness, self-support, and responsibility.